Methodological design for the assessment of physical activity and sedentary time in eight Latin American countries - The ELANS study - Ferrari, Gerson Luis de Moraes (2020)
Worldwide studies of physical activity and sedentary time have historically under-represented low- and middle-income countries due to the lack of surveillance data. The purpose of this paper is to describe the methods and procedures used for the assessment of physical activity and sedentary time in the Latin American Study of Nutrition and Health (Estudio Latinoamericano de Nutrición y Salud; ELANS). ELANS is a multicentre, cross-sectional and surveillance study of a nationally representative sample from eight Latin American countries: Argentina, Brazil, Chile, Colombia, Costa Rica, Ecuador, Peru, and Venezuela. Two instruments were used to evaluate different domains and intensities of physical activity and sedentary time: self-reported data and a triaxial accelerometer (model GT3X+). ELANS will generate important self-reported and objective information for the Latin American populations, namely: • evidence on the distribution of physical activity and sedentary time across population subgroups (e.g. sex, age, socioeconomic- and educational level). These sets of information will increase the evidence base and can help to inform future intervention strategies in Latin America; • self-reported and objective information on physical activity and sedentary time.